A subtractive proteomics approach for the identification of immunodominant Acinetobacter baumannii vaccine candidate proteins - Acar, Mustafa Burak; Ayaz-Güner, Şerife; Güner, Hüseyin; Dinç, Gökçen; Ulu Kılıç, Ayşegül; Doğanay, Mehmet; Özcan, Servet (Frontiers in Immunology, 2022)
Abstract Background: Acinetobacter baumannii is one of the most dangerous multidrug-resistant pathogens worldwide. Currently, 50-70% of clinical isolates of A. baumannii are extensively drug-resistant (XDR) and available antibiotic options against A. baumannii infections are limited. There are still needs to discover specific de facto bacterial antigenic proteins that could be effective vaccine candidates in human infection. With the growth of research in recent years, several candidate molecules have been identified for vaccine development. So far, there is no public health authorities approved vaccine against A. baumannii. Methods: The purpose of this study was to identify immunodominant vaccine candidate proteins that can be immunoprecipitated specifically with patients’ IgGs. Relaying on hypothesis that IgGs of infected person have capacity to capture immunodominant bacterial proteins. Herein, outer membrane and secreted proteins of sensitive and drug resistant A. baumannii were captured by using IgGs obtained from patient and healthy control sera and were identified by LC-MS/MS analysis. Results: By using subtractive proteomic approach, we determined 34 unique proteins which were captured only in drug-resistant A. baumannii strain via patient sera. After extensive evaluation of predicted epitope regions, solubility, membrane transverse characteristics, and structural properties, we selected several notable vaccine candidates. Conclusion: We identified vaccine candidate proteins that triggered de facto response of human immune system against the antibiotic-resistant A. baumannii. Precipitation of bacterial proteins via patient immunoglobulins was a novel approach to identify the proteins which have potential to trigger to response in patient immune system.